2016
DOI: 10.1002/hep.28359
|View full text |Cite
|
Sign up to set email alerts
|

Ustekinumab for patients with primary biliary cholangitis who have an inadequate response to ursodeoxycholic acid: A proof‐of‐concept study

Abstract: ; for the PURIFI Study Group * The interleukin (IL)-12 signaling cascade has been associated with primary biliary cholangitis (PBC). This multicenter, open-label, proof-of-concept study evaluated the anti-IL12/23 monoclonal antibody, ustekinumab (90 mg subcutaneous at weeks 0 and 4, then every 8 weeks through week 20), in adults with PBC and an inadequate response to ursodeoxycholic acid therapy (i.e., alkaline phosphatase [ALP] >1.673 upper limit of normal [ULN] after 6 months). ALP response was defined as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 36 publications
(39 reference statements)
0
68
0
Order By: Relevance
“…Although antibodies or drugs targeting the IL-12 pathway would seem to be effective, clinical trials using ustekinumab, a human monoclonal antibody directed against IL-12 and IL-23, failed to produce clinical effects in phase II trials [62]. One reason explaining this disconnection between GWAS and clinical testing results may be that clinicians typically encounter patients who have already become complicated with cholestasis; in fact, the immunological destruction of cholangiocytes occurs in the very early stages of PBC.…”
Section: Gwass On Pbcmentioning
confidence: 99%
“…Although antibodies or drugs targeting the IL-12 pathway would seem to be effective, clinical trials using ustekinumab, a human monoclonal antibody directed against IL-12 and IL-23, failed to produce clinical effects in phase II trials [62]. One reason explaining this disconnection between GWAS and clinical testing results may be that clinicians typically encounter patients who have already become complicated with cholestasis; in fact, the immunological destruction of cholangiocytes occurs in the very early stages of PBC.…”
Section: Gwass On Pbcmentioning
confidence: 99%
“…An enormous effort has been made to define the genetics and immuobiology of human autoimmue liver diseases in both human and mouse models [59][60][61][62][63][64][65][66][67][68][69][70][71][72]. Yet there remains an enormous gap between these investigative efforts and clinical translation.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical efficacy was either very limited or absent in pilot trials with rituximab [46] and with ustekinumab [47], respectively. Rituximab is an anti-CD20 monoclonal antibody that produces selective B cell depletion and potentially could ameliorate autoimmune disease by decreasing autoantibody production and antigen presentation by B cells.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, significant reduction in ALP was observed that persisted for up to 36 weeks after treatment [46]. In contrast, no overall ALP response or remission was observed at week 12 in those 20 PBC patients who were treated with ustekinumab, which is a human monoclonal antibody that specifically binds to the shared p40 protein subunit of human IL-12 and IL-23 [47]. Interestingly, in those PBC patients who showed a decline in ALP levels during ustekinumab treatment, a modulation of biochemical pathways was observed, including Th17 lymphocytes [47].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation